Bromodomain 4 inhibition leads to MYCN downregulation in Wilms tumor. Issue 2 (24th October 2021) - Woods, Andrew D.; Berlow, Noah E.; Ortiz, Michael V.; Dela Cruz, Filemon; Siddiquee, Armaan; Coutinho, Diego F.; Purohit, Reshma; Freier, Katherine E. Tranbarger; Michalek, Joel E.; Lathara, Melvin; Matlock, Kevin; Srivivasa, Ganapati; et al.
Abstract: Background: Wilms tumor is the most common childhood kidney cancer. Two distinct histological subtypes of Wilms tumor have been described: tumors lacking anaplasia (the favorable subtype) and tumors displaying anaplastic features (the unfavorable subtype). Children with favorable disease generally have a very good prognosis, whereas those with anaplasia are oftentimes refractory to standard treatments and suffer poor outcomes, leading to an unmet clinical need. MYCN dysregulation has been associated with a number of pediatric cancers including Wilms tumor. Procedures: In this context, we undertook a functional genomics approach to uncover novel therapeutic strategies for those patients with anaplastic Wilms tumor. Genomic analysis and in vitro experimentation demonstrate that cell growth can be reduced by modulating MYCN overexpression via bromodomain 4 (BRD4) inhibition in both anaplastic and nonanaplastic Wilms tumor models. Results: We observed a time‐dependent reduction of MYCN and MYCC protein levels upon BRD4 inhibition in Wilms tumor cell lines, which led to cell death and proliferation suppression. BRD4 inhibition significantly reduced tumor volumes in Wilms tumor patient‐derived xenograft (PDX) mouse models. Conclusions: We suggest that AZD5153, a novel dual‐BRD4 inhibitor, can reduce MYCN levels in both anaplastic and nonanaplastic Wilms tumor cell lines, reduces tumor volume in Wilms tumor PDXs, and should be further explored for its therapeutic potential.